0133 Feasibility and safety of nitric oxide releasing solution as a treatment for bovine mastitis. (1st October 2016) - Regev-Shoshani, G.; Martins, J.; Leemhuis, J.; Dinn, N.; Miller, C.
Abstract: Nitric oxide releasing solution (NORS) is a liquid formulation that releases nitric oxide (NO). NO is a broad, nonspecies-specific nonmicrobial nanomolecule, endogenously produced during the innate response in mammals. The objective of this study was to explore the feasibility of NORS as a potential treatment for bovine mastitis (BM). Two common pathogens found in BM (10 6 CFU/mL of Escherichia coli and Staphylococcus aureus ) were added to raw milk from healthy cows, as an in vitro model, to determine the antimicrobial efficacy of NORS at different concentrations (100–400 mM) and at two different NORS:milk ratios (2:1 and 1:1). Next, 10 ex vivo samples of milk from dairy cows presenting with clinical mastitis were obtained and treated with NORS to confirm efficacy. A dose escalating safety study was then performed using three dairy cows, where 40 mL of increasing concentrations of NORS (50–400 mM) were infused into the teat. Nitrite and methemoglobin levels were measured 5, 30, and 460 min posttreatment and nitrites in milk were measured 8 and 24 h posttreatment. Nitrite was measured by chemiluminescence, while methemoglobin was measured using a CO-Oximeter. Results show that NORS could eradicate, in vitro, both bacteria, and was dilution and time dependent. In the 2:1 ratio, NORS significantly ( P < 0.05) reduced bacterial concentration in milk both in vitro and ex vivo within 2 min, and had no detectable bacteria after 5 min of exposure. In the 1:1 ratio, a significant bacterial load reduction ( P < 0.01) occurred within 10 min and no detectable bacteria within 20 to 30 min. In the safety study we found an increase in blood nitrites ( P < 0.05) within 5 min of the NORS treatment at all concentrations. After 8 h, the blood values at all concentrations returned to baseline ( P = 0.27). Blood methemoglobin changes were nominally increased in the 5 and 30 min samples post 400 mM NORS and no detectable change was seen after 8 h. Eight hours posttreatment, before the evening milking, milk nitrites were 18 times higher than baseline, while 24 h posttreatment nitrites returned to baseline level ( P = 0.36). NORS was found to eradicate bacteria in milk and, clinically, the treatment was well tolerated. This suggests that NORS has a potential to be a safe and effective nonmicrobial treatment for BM and may allow salable milk during antimicrobial treatment of mastitis. Further, it would provide an alternative to antibiotics, thus contributing to the reduction of antibiotic drug resistance. Further studies are justified.